Segmentasi Pada Plat Kendaraan Dinas dengan Metode Deteksi Tepi Canny, Prewitt, Sobel, & Roberts - Saputra, Rizal Adi; Reskal, R; Wahyuni, Frida Mimi (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
In this day and age, technology is getting faster, making knowledge more advanced. Many people conduct research using various methods. With so many methods available, many will increasingly wonder which method to use. The author compared the official license plates using the Canny, Prewitt, Sobel, and Roberts edge detection methods. Segmentation is one of the important steps that can be used in the Number Plate Recognition system. Vehicle number plate segmentation is performed to compare four different edge detection methods, each with advantages and disadvantages. The samples we used were 28 test images consisting of 14 images at a distance of 1 meter and 14 images at a distance of 2 meters. From the test results using the canny, prewitt, sobel and roberts edge detection methods, the number of data tested is 28 images. The result is that the canny edge detection method is more accurate than the Prewitt, Sobel and Roberts edge detection method in segmenting official vehicle license plates.